1998
DOI: 10.1111/j.1572-0241.1998.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel motility in primary biliary cirrhosis

Abstract: We conclude that primary biliary cirrhosis patients present motor abnormalities of the small intestine similar to those of patients with liver cirrhosis of other etiologies. In addition, a decrease in the amplitude of small bowel contractions was also found in these patients, suggesting a myogenic involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This description means the passage of non-pathogenic bacteria, which normally colonize the gastrointestinal tract by the intestinal wall, infecting distant sites, such as mesenteric lymphnodes, spleen and liver. All this process is facilitated by several factors, including changes in intestinal flora, portal hypertension, gastrointestinal motility, and, mainly, impairment in local/systemic immune defense mechanisms, common factors in our patients [9,10,12,[29][30][31].…”
Section: Discussionmentioning
confidence: 81%
“…This description means the passage of non-pathogenic bacteria, which normally colonize the gastrointestinal tract by the intestinal wall, infecting distant sites, such as mesenteric lymphnodes, spleen and liver. All this process is facilitated by several factors, including changes in intestinal flora, portal hypertension, gastrointestinal motility, and, mainly, impairment in local/systemic immune defense mechanisms, common factors in our patients [9,10,12,[29][30][31].…”
Section: Discussionmentioning
confidence: 81%
“…Finally, in a recent study we demonstrated that acute administration of interferonalpha2b does not involve any deterioration of the GMA which could be linked to the previously reported upper abdominal symptoms in patients undergoing treatment with this drug [14]. A hint about a possibility of a disturbed gastrointestinal motility in PBC patients is provided by the paper of Madrid et al [10]. The researchers quoted described a significantly increased frequency of cluster contractions and an increased duration of phase II of the migrating motor complex in PBC patients.…”
Section: Discussionmentioning
confidence: 89%
“…The researchers quoted described a significantly increased frequency of cluster contractions and an increased duration of phase II of the migrating motor complex in PBC patients. Moreover, a decrease in the amplitude of small bowel contractions was also found, suggesting a myogenic involvement in this disease [10]. To the best of our knowledge the current study is the first one dedicated to search for GMA disturbances in the PBC patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A significantly increased frequency of clustered contractions and an increased duration of phase II of the migrating motor complex were seen in patients with liver cirrhosis [20,21]; these changes have been reported to resolve after orthotopic liver transplantation [22]. In patients with cirrhosis, bacterial overgrowth has been shown in one-third of alcoholic cirrhotics, especially those with ascites and severe liver dysfunction [13].…”
Section: Discussionmentioning
confidence: 98%